2017
DOI: 10.1007/s11657-017-0348-x
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of birth weight and length on bone mineral density and content in adolescence: The Tromsø Study, Fit Futures

Abstract: The influence of birth weight and length on bone mineral density and content in adolescence. The Tromsø Study, Fit Futures.Purpose: The influence of birth weight and length on bone mineral density and content later in life is unclear, especially in adolescence. This study evaluated the impact of birth weight and length on bone mineral density and content among adolescents.Methods: We included 961 participants from the population-based Fit Future study (2010)(2011). Dual-energy X-ray absorptiometry (DXA) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
2
3
0
1
Order By: Relevance
“…The estimated effect was modest, 0.13 (95% CI 0.02 to 0.23) and 0.31 (95% CI 0.20 to 0.41) Z ‐score higher TB BMC in boys and girls, respectively. This is in line with previous studies . This finding supports the importance of intrauterine skeletal development, as shown by others .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The estimated effect was modest, 0.13 (95% CI 0.02 to 0.23) and 0.31 (95% CI 0.20 to 0.41) Z ‐score higher TB BMC in boys and girls, respectively. This is in line with previous studies . This finding supports the importance of intrauterine skeletal development, as shown by others .…”
Section: Discussionsupporting
confidence: 94%
“…This is in line with previous studies. (8,10,46) This finding supports the importance of intrauterine skeletal development, as shown by others. (3,8,10,43) Associations between birth weight and bone strength parameters later in life have been contradictory.…”
Section: Discussionsupporting
confidence: 90%
“…Exercise during childhood and adolescence can improve bone mineral content (BMC) and areal bone mineral density (aBMD) with benefits maintained into adulthood (1). Low bone mass during adolescence is associated with increased fracture risk and osteoporosis later in life (2,3). The adolescent years are critical for bone development with up to 43 % of peak bone mass acquired during the 5-year period surrounding peak height velocity (PHV) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Dennison et al 28 also found that birth weight and body weight at one-year old determined the bone mass when they were aged about 70 years old. A series of clinical studies related to maternal nutrition and the developmental origins of osteoporosis in United States, 29 Finland, 30 Sweden, 31 Norway, 32 Australia, 33 and the Netherlands 34 also demonstrated the same phenomenon. The information of the studis is shown in Table 1.…”
Section: Evidence From Clinical Studies About Maternal Nutrition and mentioning
confidence: 77%